Guard cell activity of PIF4 and HY5 control transpiration. (March 2023) - Kelly, Gilor; Yaaran, Adi; Gal, Atara; Egbaria, Aiman; Brandsma, Danja; Belausov, Eduard; Wolf, Dalia; David-Schwartz, Rakefet; Granot, David; Eyal, Yoram; Carmi, Nir; Sade, Nir
Abstract: Whole-plant transpiration, controlled by plant hydraulics and stomatal movement, is regulated by endogenous and environmental signals, with the light playing a dominant role. Stomatal pore size continuously adjusts to changes in light intensity and quality to ensure optimal CO2 intake for photosynthesis on the one hand, together with minimal water loss on the other. The link between light and transpiration is well established, but the genetic knowledge of how guard cells perceive those signals to affect stomatal conductance is still somewhat limited. In the current study, we evaluated the role of two central light-responsive transcription factors; a bZIP-family transcription factor ELONGATED HYPOCOTYL5 ( HY5 ) and the basic helix-loop-helix (BHLH) transcription factor PHYTOCHROME INTERACTING FACTOR4 ( PIF4 ), in the regulation of steady-state transpiration. We show that overexpression of PIF4 exclusively in guard cells (GCPIF4) decreases transpiration, and can restrain the high transpiration of the pif4 mutant . Expression of HY5 specifically in guard cells (GCHY5) had the opposite effect of enhancing transpiration rates of WT- Arabidopsis and tobacco plants and of the hy5 mutant in Arabidopsis. In addition, we show that GCHY5 can reverse the low transpiration caused by guard cell overexpression of the sugar sensor HEXOKINASE1 ( HXK1, GCHXK), an established low transpiring genotype. Finally, we suggest that the GCHY5 reversion of low transpiration by GCHXK requires the auto-activation of the endogenous HY5 in other tissues. These findings support the existence of an ongoing diurnal regulation of transpiration by the light-responsive transcription factors HY5 and PIF4 in the stomata, which ultimately determine the whole-plant water use efficiency. Highlights: Elevated expression of PIF4 in guard cells reduces transpiration. Elevated expression of HY5 in guard cells enhances transpiration. Elevated expression of HY5 in guard cells can reverse the low transpiration imposed by guard cell activity of HXK1.